2010
DOI: 10.36923/jicc.v10i3.514
|View full text |Cite
|
Sign up to set email alerts
|

The blindspots and biases of intercultural communication studies: A discussion on episteme and doxa in a field

Jonas Stier

Abstract: As with other evolving fields within the realms of science the ontological assumptions and epistemological aspirations of intercultural communication studies are matters of debate and disagreement. Differently put, the very point of take-off from which studies in this field are conducted is seldom scrutinized. This being said, this paper identifies and discusses a number of blindspots and biases of intercultural communication studies – e.g. the reluctance or inability to account for analytical ethnocentrism (‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This assessment of the academic field of intercultural communication can be disputed, as both the positivistic epistemology has been criticized and alternative approaches have been suggested by a number of scholars in the field (see Blasco andGustafsson, 2004 andStier, 2010). However, important for the purposes of the present discussion, is the alternative to the essentialist, nation-approach that Falkheimer and Heide suggest: a constructionist ethnicity-approach.…”
Section: Introductionmentioning
confidence: 93%
“…This assessment of the academic field of intercultural communication can be disputed, as both the positivistic epistemology has been criticized and alternative approaches have been suggested by a number of scholars in the field (see Blasco andGustafsson, 2004 andStier, 2010). However, important for the purposes of the present discussion, is the alternative to the essentialist, nation-approach that Falkheimer and Heide suggest: a constructionist ethnicity-approach.…”
Section: Introductionmentioning
confidence: 93%
“…Consumer xenocentrism is the consumer’s preference for imported products, rejecting goods made domestically and is based on the perception that foreign products are superior to domestic goods (Rojas-Méndez and Chapa, 2020). Prior research has suggested that many consumers in developing countries prefer foreign products to domestic ones, even when they have inferior functionality (Stier, 2010) because they satisfy their need for status. This bias is attributed to consumer xenocentrism.…”
Section: Hypothesesmentioning
confidence: 99%
“…In relation to the 'cultural considerations' of children, findings in the same review of healthcare for paediatric patients show that the education of healthcare professionals tends to be ethnocentric, Eurocentric and without cultural self-reflection, that is, what Stier describes as discursive blind spots or biases. 7 Thus, rather than counteracting 'problems' or misunderstandings or merely focusing on the culture of children and parents, such biases in education or among professionals, for instance, in school healthcare services, may fuel constructions of other needs as 'different' leaving healthcare professionals without competence to encounter children with needs, values and cultures outside 'the norm'. 8 Against this background, there is a need for research addressing culture as a discourse, social construction and interactional accomplishment as well as a need to collate research on the culture(s) within the healthcare services targeting children's health and well-being beyond the paediatric context.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%